Optimalisasi Deep Learning Untuk Meningkatkan Literasi Alkitab Siswa Dalam Pendidikan Agama Kristen Di Era Digital - Pane, Pranada; Sibarani, Juana Sri Arni Sibarani (JURNAL IMPARTA, 2026)
This study aims to examine how the implementation of deep learning strategies can improve students' Bible literacy skills in Christian Religious Education subjects in the digital era. The approach used is a literature review by analyzing relevant scientific journals. The results show that deep learning strategies focusing on understanding meaning, critical thinking, and internalizing faith values significantly improve students' Bible literacy. The use of digital technology as supporting media has been proven to strengthen student engagement and learning motivation. This study recommends Christian Religious Education teachers to integrate deep learning strategies with digital media so that the learning process becomes more meaningful for students' spiritual lives.